Printed-Book Reading Habits of Pre-Service Science-Teacher Students - Imam Bachtiar (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2020)
AbstractMany studies reported that reading can improve academic achievements, critical thinking skills, confidence, social behavior, and all characters required by students to get a better job and better life. In the Disruption Era, however, many students are potentially disrupted by social media interactions that affected their reading habits. The present study was aimed to explore the reading habits of students in the printed textbook. The study was carried out in 2019, involving 469 students from three study programs of the Department of Mathematics and Science Education, i.e. Biology Education, Chemistry Education, and Physics Education. Data were collected using questionnaires in a convenience sampling method with a sample of about 70% of the population. Results show that 81% of students read printed textbooks two hours or less per day, and 53% spend less than one hour. There are a few students, however, who read textbooks more than four hours per day. Students' visit to the library is mostly (35%) 3-4 times per year and >5 times per year (33%). Reading for leisure is not very popular among the students. Multiple regression models showed that students' science textbooks, students' interest in information technology books, the number of literature read, and the number of bought-books significantly determine the duration of students' reading time. Potential methods to improve students' reading habits are discussed.AbstrakBanyak penelitian sudah melaporkan bahwa membaca dapat meningkatkan kemampuan akademis, ketrampilan berfikir kritis, perilaku sosial, dan semua karakter yang diperlukan mehasiswa untuk memperoleh pekerjaan yang bagus dan kehidupan yang lebih baik. Pada Era Disrupsi sekarang ini, banyak mahasiswa yang berpotensi terganggu oleh media interaksi sosial yang dapat mengganggu kebiasaan membaca mereka. Penelitian ini bertujuan untuk mengeksplorasi kebiasaan membaca buku teks cetakan pada mahasiswa. Penelitian dilakukan pada tahun 2019, yang melibatkan 469 mahasiswa sebagai sampel dari tiga program studi di Jurusan Pendidikan Matematika dan IPA, yaitu Pendidikan Biologi, Pendidikan Kimia, dan Pendidikan Fisika. Pengumpulan data dilakukan melalui kuesioner dengan metode convinience sampling, dengan jumlah sampel sekitar 70% dari populasi. Hasil penelitian mengungkapkan bahwa 81% mahasiswa membaca buku cetakan dua jam atau kurang per hari, dan 53% membaca kurang dari satu jam per hari. Sebagian kecil mahasiswa mengaku membaca buku cetakan lebih dari empat jam per hari. Kunjungan mahasiswa ke perpustakaan umumnya 3-4 kali per semester (35%) dan >5 kali per semester (33%). Kegiatan membaca untuk hiburan tidak populer pada mahasiswa. Model regresi berganda menunjukkan bahwa minat mahasiswa terhadap buku sains, minat mahasiswa terhadap buku teknologi informasi, jumlah buku sastra yang dibaca, dan jumlah buku yang dibeli mahasiswa, merupakan empat variabel yang dapat memprediksi lama waktu membaca mahasiswa. Cara-cara yang potensial untuk meningkatkan kebiasaan membaca mahasiswa didiskusikan.